SURGICAL WORKFLOW VISUALIZATION AS DEVIATIONS TO A STANDARD - Passaretti, Stefano; Bellio, Maura; Johnston, Helena Elizabeth Anne; Addis, Carole RJ (2024)
An aspect includes a computer-implemented method for surgical workflow visualization as deviations to a standard workflow. Surgical videos documenting multiple cases of a medical procedure are analyzed to identify variations when the medical procedure is performed multiple times by one or more service providers. According to some aspects, a visualization of one or more of the variations are output to a display device.